Slow wave propagation in plasma with non-uniformity not perpendicular to the magnetic field - Moiseenko, V.E. (Вопросы атомной науки и техники, 2019)
Slow wave propagation in 1D non-uniform plasma with tilted magnetic field with respect of direction of non-uniformity is considered. The second order differential equation describing the slow wave is derived from the Maxwell’s equations. The analysis of this equation reveals a singular point for the solutions, which could be associated with the Lower Hybrid Resonance. The condition of the resonance is found to be dependent on the tilting angle. Among two WKB solutions only one is singular. The wave vector behaves as 1/x in LHR point for the singular solution. The amplitude diverges only for x-component of the electric field. The solution describes propagating wave both to the left and to the right of the LHR point. The analytical solution obtained in the vicinity of the LHR has a special feature of having drop of its amplitude in the LHR point because of residual damping of the wave inside the LHR location. The energy flux also makes drop down there. Розглянуто поширення повільних хвиль в одновимірній неоднорідній плазмі з похилим магнітним полем щодо направлення неоднорідності. Диференціальне рівняння другого порядку, що описує повільну хвилю, виводиться з рівнянь Максвелла. Аналіз цього рівняння виявляє особливу точку для рішень, яка може бути пов'язана з нижнім гібридним резонансом (LHR). Виявлено, що умова резонансу залежить від кута нахилу. Серед двох рішень ВКБ тільки одне є сингулярним. Хвильовий вектор поводиться як 1/x в точці LHR для сингулярного рішення. Амплітуда розходиться тільки для x-компоненти електричного поля. Рішення описує хвилю, що біжить як зліва, так і праворуч від точки LHR. Аналітичне рішення, отримане в околиці LHR, має особливість, яка полягає в падінні його амплітуди в точці LHR за рахунок залишкового загасання хвилі усередині розташування LHR. Потік енергії також падає в цій зоні. Рассмотрено распространение медленных волн в одномерной неоднородной плазме с наклонным магнитным полем относительно направления неоднородности. Дифференциальное уравнение второго порядка, описывающее медленную волну, выводится из уравнений Максвелла. Анализ этого уравнения выявляет особую точку для решений, которая может быть связана с нижним гибридным резонансом (LHR). Обнаружено, что условие резонанса зависит от угла наклона. Среди двух решений ВКБ только одно является сингулярным. Волновой вектор ведет себя как 1/x в точке LHR для сингулярного решения. Амплитуда расходится только для x-составляющей электрического поля. Решение описывает бегущую волну как слева, так и справа от точки LHR. Аналитическое решение, полученное в окрестности LHR, имеет особенность, заключающуюся в падении его амплитуды в точке LHR из-за остаточного затухания волны внутри местоположения LHR. Поток энергии также падает в этой зоне.